Validation and reliability of the test of daily Activities-GLITTRE (GLITTRE-ADL TEST) to evaluate functional capacity in older adults - Gomes, Bianca Tiriba; Dal Corso, Simone; Kunitake, André Issao; Heinz, Glauber; Sousa, Ingrid Pereira; Nascimento, Beatriz Virtuoso; Souza, Wesley Alves de; Siqueira, Renato Garcia; Araújo, Robert Vitor de; Corrêa, João Carlos Ferrari; Corrêa, Fernanda Ishida (ABCS Health Sciences, 2023)
Introduction: The decline in functional capacity (FC) interferes with the functional independence of older adults, so it is important to assess the FC and use appropriate instruments for this. Objective: To investigate the Glittre Activities of Daily Living (ADL) test’s validity and reliability for assessing functional capacity in older adults. Methods: Cross-sectional study with a sample of 100 elderly (68 ± 5.16 years). To assess the convergent validity, the Six-Minute Walk Test (6MWT) and the Timed Up and Go Test (TUG) were performed. The intra-examiner test-retest of the Glittre-ADL test was performed on the same day with a 30-minute interval between repetitions and inter-examiner reliability with an interval of seven days. Results: There was a strong correlation between the Glittre-ADL test and the 6MWT (r= -0.75; p<0.001) and the TUG (r=0.77; p<0.001). The intra-examiner and inter-examiner reliability was excellent (ICC)=0.91 and 95% CI=0.14-0.97; p<0.001 and ICC=0.91; 95% CI: 0.86-0.94; p<0.001, respectively). Conclusion: The Glittre-ADL test demonstrated that it is valid and that its reliability is adequate to assess functional capacity in older adults.